Photon counting histogram for one-photon excitation. - Perroud, T; Huang, B; Wallace, M; Zare, R (2003)
An advance that counts! A method is presented for analyzing single-molecule behavior using one-photon excitation of fluorescence. It is based on the photon counting histogram (PCH) procedure that has enjoyed much success for two-photon excitation, but has not previously been applied to one-photon excitation. This corrected PCH model is able to resolve fluorescent species with different degrees of brightness, for example, a mixture of tetramethylrhodamine-5′-maleimide and Cy3-maleimide (see graph). Because one-photon excitation is often much easier to do than two-photon excitation, this method has the potential to be widely used and represents an important advance in the field of single-molecule spectroscopy.